Qualitative Exploration of Causal Factors Influencing the Divorce Process Based on the Lived Experiences of Divorced Couples - Kerdegar , Mitra; Barzegar, Majid; Baghooli , Hossein; Kouroshnia, Maryam (Mental Health and Lifestyle Journal, 2025)
Divorce, as one of the most serious social and psychological challenges, has extensive consequences for individuals, families, and society. Identifying the causal factors contributing to the divorce process can help achieve a deeper understanding of this phenomenon and provide preventive strategies. The present study aimed to qualitatively examine the causal factors influencing the emergence of the divorce process based on the lived experiences of divorced couples. The study employed a qualitative method using semi-structured interviews. The interviews continued until data saturation was reached, and 10 couples were interviewed. To enrich the data, both broad and probing questions were used. After data collection, the data were analyzed through thematic analysis. To ensure the trustworthiness and validity of the findings, the four criteria proposed by Lincoln and Guba (credibility, transferability, confirmability, and dependability) were employed, including participant checking, confirmation by academic supervisors and advisors, external auditing of the data analysis, and purposeful sampling of participants with diverse experiences. The findings indicated that the causal conditions contributing to divorce in the lived experiences of the studied couples resulted from a complex interplay of cultural, psychological, and social factors. Data analysis showed that dysfunctional family patterns and the intergenerational transmission of maladaptive schemas, the symbolic gender system and traditional beliefs about the roles of men and women, difficulties in emotion regulation and a lack of psychological literacy, strong dependency on the family of origin and interference by relatives, hasty marriages and uninformed partner selection, and dysfunctional marital beliefs were among the most significant causal conditions. Moreover, factors such as marital infidelity, lack of physical attractiveness, and neglect of personal care were highlighted in the couples’ narratives as the ultimate indicators of emotional and psychological disengagement. The analytical synthesis of the study suggests that causality in the divorce process is not a single-factor phenomenon but rather a complex overlap of three levels of causality: structural causality (gender attitudes and cultural pressures), psychological causality (lack of emotional and communication skills), and intergenerational causality (transmission of damaging family patterns). Ultimately, divorce in the cultural context of Shiraz reflects the tension between entrenched traditions and contemporary needs for an egalitarian, emotionally supportive, and dialogue-based relationship.